Spatial optimization of nutrient recovery from dairy farms to support economically viable load reductions in the Chesapeake Bay Watershed. (April 2023) - Femeena, P.V.; Costello, C.; Brennan, R.A.
Abstract: CONTEXT: To promote circularity in agricultural systems, the utilization of aquatic vegetation for ecological wastewater treatment is a potential mechanism to capture and upcycle nutrients. Agricultural wastewater is an excellent growing medium for aquatic plants like duckweed, offering opportunities for wastewater treatment and conversion of harvested biomass into bio-based products, including protein-rich livestock feed, which can potentially replace conventional soil-based crops such as alfalfa. OBJECTIVE: We hypothesize that nitrogen (N) and phosphorus (P) loadings to the Chesapeake Bay Watershed (CBW) can be reduced via replacing alfalfa cultivation with manure-grown duckweed by: a) reducing excess manure application on agricultural fields; b) reducing synthetic fertilizer application on alfalfa croplands; and c) decreasing the release of fixed N back into the environment from the decomposition of alfalfa crop residue. METHODS: This study developed an optimization framework to identify locations where alfalfa-to-duckweed replacement could be theoretically employed to minimize N and P loads into the CBW. A relative effectiveness (RE) indicator representing landscape-specific nutrient delivery capacity was included within the framework. Using county-level data on alfalfa yields, cropping area, and nutrient inputs from alfalfa croplands and dairy manure, we identified alfalfa cultivation areas that could be removed and replaced with full or partial duckweed cultivation and land conservation for optimal benefits. RESULTS AND CONCLUSIONS: At the county scale, counties in Pennsylvania (especially Lancaster and adjacent regions) with widespread farming operations and high RE values consistently indicated the greatest benefit by replacing large areas of alfalfa cultivation (> 80% in each county) with duckweed. Using nutrient load minimization as the primary objective function, a 2.9% N reduction and 2.4% P reduction can be achieved at the watershed scale by converting only 7.6% of the total alfalfa cropland area into duckweed farms. Upon introducing production cost minimization as a competing second objective function, up to 12.8% N reduction and 9.2% P reduction are possible with a 40% decrease in the alfalfa cropping area. A 10-year economic analysis demonstrated the possibility for superior return on investment with this approach, leading to almost seven times the baseline net revenue with alfalfa production, primarily attributed to the higher protein content and corresponding revenue potential of duckweed. SIGNIFICANCE: Many different constraints on alfalfa production (ex., maintaining some baseline production) and duckweed replacement strategies (ex., utilization of decommissioned alfalfa area vs. soil conservation) were used in this study, which offer a wide range of optimal solutions that consider both environmental and economic tradeoffs. Graphical abstract: Unlabelled Image Highlights: Duckweed can be used to recover nitrogen (N) and phosphorus (P) from dairy wastewater. Nutrient loadings to the Chesapeake Bay Watershed (CBW) can be reduced by replacing alfalfa cultivation with duckweed. Spatial optimization identified locations for alfalfa-to-duckweed replacement to minimize N and P loads to the CBW. A load reduction of 12.8% N and 9.2% P is possible with a 40% decrease in alfalfa area. High protein duckweed yields almost 7 times the baseline net revenue of alfalfa production.